Experimental studies of the attention characteristics of elementary school students studying chess - Khachatryan, Armine; Sargsyan, Anzhela
Since 2011, "chess" has been included in the Republic of Armenia's state standard of general education and is taught as an obligatory subject in grades 2-4. This breakthrough attracted the curiosity of a diverse group of scientists, particularly psychologists. In this paper, we present the process of experimental studies conducted by psychologists of the Khachtur Abovyan ASPU's Chess Scientific Research Institute from 2013 to the present. The study's goal is to highlight the process of demonstrating and developing attention skills when mastering and teaching the "Chess" subject.
Keywords: Elementary school